Inspiring nurses’ sustainability mindset: Exploring the Mediating Role of Organizational Culture on the relationship between Pro-social Leader behaviors and nurses’ sustainability consciousness - Amal Diab Ghanem Atalla; Wafaa Hassan Mostafa; Mohamed Saad Saleh Ali (BMC Nursing, 2024)
Abstract Background Since nurses are at the frontline of healthcare delivery, their actions and understanding of the environment have a big impact on how long healthcare systems can last. It is essential to comprehend the elements that impact nurses’ sustainability consciousness to encourage ecologically conscious actions in the healthcare industry. Aim This study aimed to explore the relationship between pro-social leader behaviors and nurses’ sustainability consciousness and testify to the mediating role of organizational culture in this relationship. Design A cross-sectional descriptive correlational design by STROBE criteria was used. Methods and tools An approach to a judgmental non-probability sampling technique was employed to obtain data from 350 nurses in an Egyptian hospital. Three measurement surveys were employed: Organizational Culture Survey, Prosociality Scale, and, Sustainability Consciousness Questionnaire (SCQ-S). Relationships were shown using structural equation modeling and descriptive and inferential statistics. Results 53.4% of nurses have high perceptions of organizational culture, and the majority of nurses (85.7%) have high perceptions of prosocial leader behaviors. Furthermore, 60.9% of nurses have high perceptions of sustainability consciousness. Additionally, Prosocial leader behaviors positively correlated with organizational culture (r = 0.129) and nurses’ sustainability consciousness (r = 0.274). The indirect effect of prosocial leader behaviors on nurses’ sustainability consciousness through organizational culture is calculated by multiplying the coefficients of both direct effects (0.129 * 0.159 = 0.811). This means that for each unit increase in prosocial leader behaviors, we would expect a 0.811 unit increase in nurses’ sustainability consciousness through the mediating effect of organizational culture. The model appears to match the data well based on the model fit parameters (CFI = 1.000, IFI = 1.000, RMSEA = 0.114). Conclusions The study highlights the impact of pro-social leader behaviors on nurses’ sustainability consciousness through the organizational culture as a mediating factor. Nursing Implications: Findings from this research can promote environmental stewardship and sustainable practices in the healthcare sector by illuminating the elements that can encourage and support a sustainability-oriented mindset among nurses. To promote a more sustainable future for the nursing profession, the findings can guide activities in nursing education, corporate culture transformation, and leadership development.